2008
DOI: 10.1038/eye.2008.74
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous management in penetrating trauma: primary repair and secondary intervention

Abstract: Ocular trauma involving the vitreous produces a very wide range of pathology, the treatment of which can confuse. In the past, the prognosis for vision following such injuries was poor. Modern closed intraocular surgical techniques have transformed the management of penetrating trauma and allowed salvage of vision in many previously hopeless cases. However, many controversies remain, including the timing of surgical intervention, the use of encircling buckles, and the type of internal tamponade. This article w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
2
25
0
1
Order By: Relevance
“…all intraocular injuries amenable to treatment are addressed immediately after the wound has been closed; fig. 2) can be performed [8]. The advantages of this approach are numerous: the risk of a subsequent development of endophthalmitis is eliminated; should an infection already have started, it can be properly dealt with; all tissue pathologies that do not represent irreversible damage may be treated (e.g.…”
Section: Open-globe Traumamentioning
confidence: 99%
“…all intraocular injuries amenable to treatment are addressed immediately after the wound has been closed; fig. 2) can be performed [8]. The advantages of this approach are numerous: the risk of a subsequent development of endophthalmitis is eliminated; should an infection already have started, it can be properly dealt with; all tissue pathologies that do not represent irreversible damage may be treated (e.g.…”
Section: Open-globe Traumamentioning
confidence: 99%
“…These two factors have helped save many eyes that would have previously been enucleated. 1 Histological studies showed the important role of blood in creating a posterior vitreous detachment (PVD) after about a week of the injury. Proliferation of cells on the surface of the retina and vitreous subsequently leads to tractional retinal detachment, which usually occurs after 6 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale of encirclement is to reduce the circumference of the vitreous base and thereby relieve traction on the peripheral retina. 1,10 The goal of our study is to examine how advanced microsurgical techniques can optimize the management of perforating ocular injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 6 despite a delay in the intervention of 21 days, spontaneous PVD at the time of surgery was present in only 24.5% of the patients. As stated in the review by Aylward,7 although the question of best timing for vitrectomy in penetrating trauma is likely to remain controversial for some time, a flexible approach is recommended.…”
mentioning
confidence: 98%